Unpresidented : a biography of Donald Trump - Brockenbrough, Martha (Feiwel and Friends, 2018)
"Discover the incredible true story of America's forty-fifth president : his questionable political and personal conduct and his unprecedented rise to power. Richly informed by original research, Unpresidented is a gripping and important read"-- Dustjacket.